Repeated potassium iodide exposure during pregnancy impairs progeny's brain development. (15th May 2019) - Lebsir, Dalila; Guemri, Julien; Kereselidze, Dimitri; Grison, Stephane; Benderitter, Marc; Pech, Annick; Cohen, David; Benadjaoud, Mohamed Amine; Lestaevel, Philippe; Souidi, Maâmar
Abstract: Protracted radioiodine release may require repeated intake of potassium iodide (KI) to protect thyroid gland. It is well established that iodine excess inhibits transiently the thyroid function. As developing fetus depends on maternal thyroid hormones (TH) supply, more knowledge is needed about the plausible effects that repeated KI intake can cause in this sensitive population, especially that even subtle variation of maternal thyroid function may have persistent consequences on progeny brain processing. The aim of this study is to assess the consequences of repeated intake of KI during pregnancy on the progeny's thyroid function and brain development.To do so pregnant Wistar rats received KI over eight days, and then thirty days after the weaning, male progeny was subjected to behavior test. Pituitary and thyroid hormones level, anti-thyroid antibodies level, organs morphology, gene expression and global DNA methylation were assessed. Thirty days after the weaning, KI-exposed male progeny showed an uncommon hormonal status, characterized by a decrease of both thyroid-stimulating hormone (− 28%) and free thyroxine (− 7%) levels. Motor coordination was altered in KI-exposed male progeny. At the cerebellar level, we observed a decrease of mRNA expression of DCX (− 42%) and RC3 (− 85%); on the other hand, at the cortical level, mRNA expression of MBP (+ 71%), MOBP (+ 90%) and Kcna1 (+ 42%) was increased.To conclude, repeated KI prophylaxis is not adequate during pregnancy since it led to long-term irreversible neurotoxicity in the male progeny. Highlights: This study evaluates the impact of in utero KI intake on the progeny brain processing. In utero exposure to KI impairs progeny motor coordination. Our results will contribute to the evolution of iodine guidelines in case of pregnancy.